UKRAINIAN LITERATURE FOR CHILDREN AND ETHICAL EDUCATION - Harmash, Liudmyla; Khalanska, Natalia; Hordieieva, Olena; Razumenko, Iryna; Tyshchenko, Tetyana (Revista Inclusiones, 2020)
The article considers the narrative approach to the analysis of ethical issues of literature for children such as humanism, patriotism, sincerity, love of nature and so on. Through the work of one of the most famous Ukrainian writes, we examine the ratio of two types of consciousness – a child’s one and an adults’ one. The result should help better understanding the narrative organization features in literature for children. It is shown that the child's consciousness is characterized by increased intensity of the cognitive processes. The development of ethical ideas in the child’s mind is analised from the perspective of cognitive narratology.